BEKE, REBECCA. (2011). Las voces de los otros en el discurso académico. Caracas: Universidad Central de Venezuela, 176 paginas. ISBN: 978-980-7283-12-0 - Cisneros, Mariela (Akademos, 2018)
Reseña de Beke, Rebecca. (2011). Las voces de los otros en el discurso académico. Caracas: Universidad Central de Venezuela, 176 paginas. ISBN: 978-980-7283-12-0